Analisis Kualitas Website MAN 2 Kota Serang menggunakan Metode Webqual 4.0 dan Importance Performance Analysis (IPA) - Dian Eka Pratiwi; Buce Trias Hanggara; Intan Sartika Eris Maghfiroh (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The use of technology affects social life to support each individual's needs. One of the uses of technology is a website. The MAN 2 Serang City website acts as an intermediary for educational service information. On the MAN 2 Serang City website, there are several problems, namely the lack of information about majors that often causes students to choose the wrong major, the absence of information about student interest and talent services to support student activities and the use of online services on the MAN 2 Serang City website which is still minimal and the need to measure and analyze the quality of the MAN 2 Serang City website based on user satisfaction. This research uses the Webqual 4.0 method and Importance Performance Analysis (IPA) to be able to produce maximum improvement evaluation. Based on the results of the suitability analysis, the MAN 2 Serang City website has an overall value of 91.87% and the results of the gap analysis of -0.34 which shows that the quality of the website has not been able to satisfy users. The results of quadrant mapping show that the first quadrant has 6 attributes, the second quadrant has 4 attributes, the third quadrant has 4 attributes, and the fourth quadrant has 5 attributes. The results of the hypothesis show that the usability variable does not significantly affect user satisfaction. Variables in the quality of information and variables in the quality of service interactions have a significant effect on user satisfaction. Providing suggestions and recommendations for improvement focuses on the first and third quadrants of the 3-dimensional Webqual 4.0.